Performance Evaluation of Chosen Graph Database Systems - Zbyszko KROLIKOWSKI1; Izabela ROJEK2; Bartlomiej DEBICKI3 (Communications of International Proceedings, 2021)
The paper presents the performance evaluation of chosen graph databases. It presents the basics of graph databases, including selected elements of graph theory, graph database query languages, i.e. Cypher Query Language used in Neo4j and Gremlin, a procedural language used in most graph database systems. Selected areas of graph database applications are also discussed. The paper also shows the characteristics of some of the most popular graph database systems, including Neo4j, selected as one of two systems for performance tests. The second system was ArangoDB, selected in the performance tests as a representative of other systems. The experiment was aimed at comparing the times of data writing / searching in both graph databases subject to comparison.
Keywords: Graph Databases; Neo4j; Arangodb; Performance Evaluation.